"You Gotta Have a Plan so You Won't Get Caught": Managing the Risks of Street Tagging. Issue 9 (2nd September 2021) - DeShay, Rashaan A.; Vasquez, Arthur G.; Vieraitis, Lynne M.
ABSTRACT: Exploring offender decision-making is important to understanding criminal behavior as well as assisting in the creation of criminal justice policy. We analyzed interviews with 25 active juvenile street taggers to identify the sanction avoidance strategies they used to minimize the risk of detection and apprehension by law enforcement and other social control agents. The data suggested that despite the risks associated with street tagging, participants engaged in planning prior to their offending and relied on a number of strategies to reduce the chance of detection and arrest. The findings also revealed that efforts to be invisible to social control agents were complicated by their desire for visibility for their tags. This study expands the existing body of literature by examining active juvenile street taggers and suggests the need for scholars to continue to study restrictive deterrence techniques for varying types of offenders.